Pengaruh Ukuran Butir Agregat Eps Modifikasi Terhadap Kuat Tekan Beton Ringan Yang Menggunakan Pasir Batu Apung - Kusnadi, Kusnadi; Imran, Imran; Rauf, Iksan (Fakultas Teknik Universitas Khairun, 2025)
Lightweight concrete using pumice sand and modified Eps waste needs to be continuously developed to produce construction materials that prioritize the use of local and environmentally friendly materials. This study aims to determine the effect of the grain size of modified Eps aggregate as coarse aggregate on the compressive strength of lightweight concrete using pumice sand as fine aggregate. The specimens in this study used concrete cylinders with a diameter of 100 mm and a height of 200 mm. The specimen was tested with a compression test at the age of 28 days. The test results showed that the larger the size of the modified Eps aggregate tended to increase the compressive strength value, but the size of the modified Eps aggregate that was too large reduced its density and had an impact on reducing the compressive strength of the concrete